ANALYSIS OF ASSESSMENT INSTRUMENTS IN MADRASAH SCHOOLS WITH EVALUATION THEORIES - Amin, Khoirul; Sari, Ana Kurnia (Proceeding of International Conference of Islamic Education, 2024)
This article will examine how evaluation tools in madrasah schools can be analyzed using various evaluation theories. This research method is a literature study which aims to understand more deeply about evaluation tools, especially in the context of this problem. This literature study involves collecting data through searching and reviewing literature relevant to the research topic. The selection of literature sources was carried out based on predetermined inclusion and exclusion criteria. Evaluation tools are devices used by teachers to collect, analyze and measure data, as well as apply various information obtained to assess the achievement of learning objectives, which include students' knowledge, skills and attitudes. In analyzing evaluation tools in Madrasah schools, it is important to integrate the principles of several evaluation theories so that the evaluation tools are more effective and appropriate to the typical Madrasah educational context. In addition, the tool evaluation process must be ongoing so that it remains relevant and useful in the learning process. Several evaluation theories that can be a guide for analyzing evaluation tools in Madrasah Schools are Utilitarian Theory, which focuses on the use of evaluation results to improve the effectiveness of programs or curricula. Analysis of evaluation tools must consider whether the results can truly improve the quality of education in Madrasas. Furthermore, Stakeholder Theory emphasizes the importance of taking into account the interests of all parties involved in Madrasah education, including students, teachers, parents and authorities. Evaluation tools should reflect their needs and expectations. Finally, Constructivist Theory emphasizes that evaluation must actively involve students in the learning process. Therefore, evaluation tools must be designed to encourage deep understanding and knowledge building by students.